Positive Politeness Strategies in "The Karate Kid" Movie - Peni, Ni Wayan; Maharani, Sang Ayu Isnu; Beratha, Ni Luh Sutjiati (Apollo Project: Jurnal Ilmiah Program Studi Sastra Inggris, 2023)
This research entitled “Positive Politeness Strategies in The Karate Kid Movie” aims at identifying the types of positive politeness strategies used in The Karate Kid movie and analyzing the response occurred to the realization of positive politeness strategies in The Karate Kid movie. The data of this research were taken from the transcript of the conversation in the movie. The data were in the form of words, phrases, and sentences of the characters. The method and technique to collect the data was documentation and supported by note-taking technique. The method and technique of analyzing the data was qualitative method and supported by triangulation technique. The method and technique of presenting analysis was informal method and supported by descriptive technique. The theory of Brown and Levinson’s (1987) was used to analyze the types of positive politeness strategies and Levinson’s (1983) theory was used to analyze the types of response occurred to the realization of positive politeness strategies. The results found there were 9 types of positive politeness strategies which used by the characters in The Karate Kid movie namely, strategy 1 Notice, attend to H (his/her interests, wants, needs, goods), strategy 2 Exaggerate (interest, approval, sympathy with H), strategy 4 Use in group identity markers, strategy 5 Seek agreement, strategy 9 Asserting/presupposing S’s knowledge of and concern for H’s wants, strategy 10 Offer, promise, strategy 11 Be optimistic, strategy 12 Include both S and H in the activity, and strategy 13 Give (or ask for) reasons. Regarding to the response occurred to the realization of positive politeness strategies both preferred response and dispreferred response were used by the characters to the realization of positive politeness strategies in The Karate Kid movie. Keywords: Positive Politeness Strategies, Politeness Strategies, The Karate Kid